Introduction to the Special Issue: Economic Challenges Facing Pastoral Leaders - Manion, Matthew F. (Review of religious research, 2025)
This Special Issue of Review of Religious Research, entitled "Economic Challenges Facing Pastoral Leaders," publishes high-quality empirical research studies that address the financial and economic challenges faced by churches and pastoral leaders. The aim is to document and better understand the nature and scope of those challenges and the strategies used to address them. Studies that address these challenges and strategies focus on the impact of the financial challenges within a religious institution, as well as how church leaders are responding to the financial pressures, including the strategies and tactics employed to counteract the threats. As a collection of articles, the Special Issue seeks to advance researcher understanding of the financial headwinds faced by church leaders and the responses to those challenges. For pastoral leaders and practitioners, these studies seek to promote financial literacy and more effective responses to the economic challenges leaders face. The issue includes an original research article, four research notes, and two book reviews.